PRACTICAL APPLICATION OF DABIGATRAN ETEXILATE FOR STROKE PREVENTION IN PATIENTS WITH ATRIAL FIBRILLATION - E. D. Kosmacheva; S. G. Kanorskiy; A. A. Kastanayan; N. V. Haylo; D. B. Goltyapin; E. A. Lipnitskaya; M. E. Statsenko (Рациональная фармакотерапия в кардиологии)
Disadvantages of vitamin K antagonist warfarin and the benefits of new anticoagulants, including dabigatran etexilate, in the stroke prevention in patients with atrial fibrillation are considered. Factors that influence the choice of dabigatran dose in different individuals are discussed. Dabigatran treatment in special conditions is considered: during stroke development; in electrical or pharmacological cardioversion; in invasive or surgical procedures; during bleeding. Possible organizational system of thromboembolic events prevention in patients with atrial fibrillation is presented.